Barriers and Enablers to the Regulation of Sanitation Services: A Framework for Emptying and Transport Services in Sub-Saharan African Cities - Lerebours, Alix; Scott, Rebecca; Sansom, Kevin; Kayaga, Sam (Frontiers in Environmental Science, 2022)
Onsite sanitation is the dominant form of sanitation in Sub-Saharan African cities. Services for emptying the fecal sludge from these facilities and transporting it to safe disposal or treatment plants are crucial to public and environmental health. While these services are becoming increasingly regulated, implementation of the regulation remains a challenge. Through a multiple-case study anchored in the Contextual Interaction Theory, this research investigated the barriers and enablers to regulating emptying and transport services for fecal sludge. Looking at the cases of Kampala, Lusaka, and Freetown, this research found that both the content of the regulation and the regulatory process (initiation, creation or reform through to implementation) play a key role in the extent to which the regulation is or can be implemented. New elements relating to the knowledge, motivation, and resources of all stakeholders are identified as crucial to achieve regulated services. The findings have resulted in a framework that identifies the key elements to consider when regulating services. This framework would prove useful to practitioners and researchers engaged through all stages of creating, implementing, and evaluating regulatory practices.